2021
DOI: 10.3389/fmicb.2021.704302
|View full text |Cite
|
Sign up to set email alerts
|

Complete Replacement of Nitrite With a Lactobacillus fermentum on the Quality and Safety of Chinese Fermented Sausages

Abstract: This study investigated the positive effects of complete replacement of nitrite with a Lactobacillus fermentum on the quality and safety of Chinese fermented sausages, and evaluated the risk of this strain. The effects of the strain on pH, color, nitrite, thiobarbituric acid reactive substances (TBARS), total volatile basenitrogen (TVB-N), metmyoglobin (Met-Mb), biological amines, free amino acid content, and sensory index have been studied. The results revealed that the strain reduced the pH of the sausages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Moreover, Lactobacillus fermentum detected in this study has been confirmed to inhibit the production of histamine by Xu et al [23]. Dias et al [48] also found that Staphylococcus equorum promoted the reduction of histamine on traditional dry-cured sausage.…”
Section: Biogenic Amines Analysissupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, Lactobacillus fermentum detected in this study has been confirmed to inhibit the production of histamine by Xu et al [23]. Dias et al [48] also found that Staphylococcus equorum promoted the reduction of histamine on traditional dry-cured sausage.…”
Section: Biogenic Amines Analysissupporting
confidence: 65%
“…The TVBN values were estimated according to methods of Xu et al [23]. Ten grams of samples were taken into a conical flask with 100 mL distilled water, and immersed for 30 min with shaking.…”
Section: Total Volatile Basic Nitrogen (Tvbn) Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Salama et al [ 39 ] applied the red pigment extracted from Trichoderma purpureum to meat products and found that the pigment not only gave the meat products a good color even after steaming and frying, but also extended the shelf life of the food. Xu and Zhu [ 40 ] reported that L. plantarum could reduce the sausage pH, accelerate the acidification and gelatinization process, and add good color to the meat products and reduce the content of nitrite residues in the sausage, as well as prevent fat oxidation, protein decomposition, and myoglobin oxidation, and increase the content of free amino acids.…”
Section: Effects Of Lab On Substance Metabolism and The Flavor Of Fer...mentioning
confidence: 99%
“…The volume was adjusted to 100 ml with simulated tear fluid. The solution was filtered through a 0.45-mm filter membrane and Norfloxacin concentration was then determined at 273nm by using UV-Vis spectrophotometer 13 .…”
Section: Drug Contentmentioning
confidence: 99%